The Determinants towards Mobile Commerce Adoption among University Students in Malaysia: A Conceptual Framework - Abdull Rahman, Nurul Labanihuda; Hassan, Shahizan (UUM Press, 2017)
The rapidly emerging wireless and mobile network which offers a new platform to sell products efficiently is known as M-commerce (mobile commerce). While numerous studies have been carried out on technology adoption, not much is known about mobile commerce adoption in Malaysia, namely the governing factors and appropriate models that could explain the behaviours of young generations on the use of mobile commerce. Therefore, this paper attempts to propose a model of mobile commerce adoption in Malaysia by integrating the models of TAM3, and Individualism-Collectivism at Individual-Level (ICAIL) as moderating variables in the context of mobile commerce. This paper presents a basic understanding of the concept of mobile commerce and its business characteristics. It also describes several issues pertaining to mobile commerce from previous studies. Based on a thorough literature analysis, a model of determinants of mobile commerce adoption is presented. The findings from this study are important to the advancement of knowledge in the retail or service industries, specifically for members of the younger generation who are early and enthusiastic adopters of new technologies. The findings from this study allow a better understanding of their usage behaviour in employing M-commerce in their daily lives.